2019
DOI: 10.1016/j.vas.2019.100052
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic interaction between bovine tuberculosis (bTB) and Johne's disease in bTB highly prevalent dairy farms of Uruguay

Abstract: Highlights In Uruguay (Uy), bTB highly prevalent dairy herds have emerged. Johne's disease (JD) control programs lack at the national level in Uy. In high prevalence coinfected herds, bTB- and JD-diagnosis interact. An integrated control program is needed for high prevalent coinfected dairies in Uy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…The effect of the inoculation of PPDb during bTB‐intradermal testing on the results of subsequent bTB diagnostic assays (cellular and humoral immune response tests) in both bTB‐infected and bTB‐free animals has been well documented and is generally accepted 34–38 . However, reports on the effect of PPDb inoculation on the diagnostic response for JD are conflicting 9 15 17 26 39–43 . As with bTB, JD has its own physiopathological characteristics that hamper its diagnosis, such as its long incubation period and the delayed antibody response 44 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the inoculation of PPDb during bTB‐intradermal testing on the results of subsequent bTB diagnostic assays (cellular and humoral immune response tests) in both bTB‐infected and bTB‐free animals has been well documented and is generally accepted 34–38 . However, reports on the effect of PPDb inoculation on the diagnostic response for JD are conflicting 9 15 17 26 39–43 . As with bTB, JD has its own physiopathological characteristics that hamper its diagnosis, such as its long incubation period and the delayed antibody response 44 45 .…”
Section: Discussionmentioning
confidence: 99%
“…This relatively low accuracy of the intradermal tests in Uruguay suggests that the bTB-control program may suffer from limited Se in heavily infected herds (~53%), what could lead to the persistence of infected animals in the dairy cattle population over time. Possible explanations for this finding include: presence of other infections that could compromise the reliability of bTB diagnostic tests such as Johne's disease, that is prevalent in dairy herds in Uruguay and whose impact on bTB diagnosis has been already suggested in the country (14), a high proportion of animals in an advanced stage of disease (state of anergy) (30, 57), what could be plausible given the high prevalence of infection in the tested herds, along with other factors associated with the performance of the technique itself or the animals tested, which, with the consolidation and intensification of the industry, may have contributed to the re-emergence of bTB observed in the last decade (14).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the number of bTB-positive dairy herds detected every year, the within-herd prevalence in infected farms, and the time from outbreak detection to control has increased in Uruguay despite measures implemented as part of the national bTB control program (12, 13). The evolution of the dairy industry in the country, characterized by an increase in herd sizes and production intensification, has been associated with the limited success of bTB-control in recent years (12, 14). Additionally, insufficient sensitivity of bTB diagnostic tests may also contribute to the persistence of potentially infectious individuals in the herd that can further spread the disease within and between herds (15).…”
Section: Introductionmentioning
confidence: 99%
“…Within the past two decades, however, the number of bTB‐infected dairy herds, the within‐herd bTB prevalence and the time required from detection to regaining the officially tuberculosis‐free status (OTF) increased (Picasso‐Risso, Gil, et al, 2019; Picasso‐Risso, Perez, et al, 2019) leading to unprecedented challenges in the control of bTB in Uruguay. The difficulty in controlling bTB has been associated with changes in dairy demographic structure and management (Picasso et al., 2017; Picasso‐Risso, Gil, et al, 2019; Picasso‐Risso, Perez, et al, 2019), including larger herds (>360 animals), higher animal density (DIEA, 2018), increased animal movements and more intensive animal rearing than traditional dairy farming prior to the 1990s (Picasso et al., 2017). In this context, the question is whether the current Uruguayan bTB programme is sufficient to control bTB in herds once the infection is confirmed and some level of within‐herd transmission is suspected.…”
Section: Introductionmentioning
confidence: 99%
“…An integrated within‐ and between‐herd model has been parameterized and validated to evaluate the performance of risk‐targeted bTB surveillance using the current test‐and‐slaughter bTB strategies in Uruguay (VanderWaal et al., 2017). However, previous studies have suggested that the sensitivity of the test‐and‐slaughter programme is impaired in high prevalence dairy herds in Uruguay (Picasso‐Risso, Gil, et al, 2019; Picasso‐Risso, Perez, et al, 2019), and given that depopulation of these large herds is not economically, logistically or socially feasible, the use of alternative diagnostic in vitro assays is a reasonable alternative strategy to evaluate for control in these herds. In this study, we aimed to assess the effectiveness of different alternative bTB‐control strategies, to ultimately elucidate the optimal option for control in bTB‐high prevalence dairy herds in Uruguay when depopulation is not an alternative.…”
Section: Introductionmentioning
confidence: 99%